Learning Community Management Planning at SMP Negeri 54 Batam City - Herizon; Agung Kuswantoro (Universitas Pendidikan Mandalika, 2025)
This study aims to describe the management planning of the learning community in SMP Negeri 54 Batam City in order to improve teacher competence and learning quality. The research background is based on the importance of learning communities as a forum for collaboration, reflection, and professional development of educators in the era of Freedom of Learning. The research uses a qualitative approach with data collection techniques through interviews, documentation studies, and observations. The research informants included school principals, vice principals for curriculum, heads and members of the learning community, teachers, and student representatives. The results of the study show that the management planning of the learning community at SMP Negeri 54 Batam City includes four main stages: (1) coordination meetings to equalize perceptions, form vision-missions, and prepare work programs; (2) the formation of a learning community team with a clear division of tasks; (3) internal and external socialization to increase participation and support; and (4) the provision of supporting facilities and infrastructure such as meeting rooms, projectors, internet connections, and collaborative media. The obstacles faced include the limitations of modern facilities such as Smart TVs, exclusive special rooms, and documentation tools. The conclusion of the study shows that systematic and participatory learning community management planning is able to encourage a culture of continuous learning among teachers, although there is still a need to improve facilities and strengthen socialization strategies. The results of this research are expected to be a reference for other schools in developing an effective learning community and have a positive impact on the quality of learning. Keywords: Management, Planning, Learning Community, Teacher Competence. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan perencanaan manajemen komunitas belajar di SMP Negeri 54 Kota Batam dalam rangka meningkatkan kompetensi guru dan mutu pembelajaran. Latar belakang penelitian didasari oleh pentingnya komunitas belajar sebagai wadah kolaborasi, refleksi, dan pengembangan profesional pendidik di era Merdeka Belajar. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, studi dokumentasi, dan observasi. Informan penelitian meliputi kepala sekolah, wakil kepala sekolah bidang kurikulum, ketua dan anggota komunitas belajar, guru, serta perwakilan siswa. Hasil penelitian menunjukkan bahwa perencanaan manajemen komunitas belajar di SMP Negeri 54 Kota Batam mencakup empat tahap utama: (1) rapat koordinasi untuk menyamakan persepsi, membentuk visi-misi, dan menyusun program kerja; (2) pembentukan tim komunitas belajar dengan pembagian tugas yang jelas; (3) sosialisasi internal dan eksternal untuk meningkatkan partisipasi dan dukungan; serta (4) penyediaan sarana dan prasarana penunjang seperti ruang pertemuan, proyektor, koneksi internet, dan media kolaboratif. Kendala yang dihadapi meliputi keterbatasan fasilitas modern seperti Smart TV, ruang khusus yang eksklusif, dan alat dokumentasi. Kesimpulan penelitian menunjukkan bahwa perencanaan manajemen komunitas belajar yang sistematis dan partisipatif mampu mendorong budaya belajar berkelanjutan di kalangan guru, meskipun masih diperlukan peningkatan fasilitas dan penguatan strategi sosialisasi. Hasil penelitian ini diharapkan dapat menjadi acuan bagi sekolah lain dalam mengembangkan komunitas belajar yang efektif dan berdampak positif terhadap kualitas pembelajaran. Kata kunci: Manajemen, Perencanaan, Komunitas Belajar, Kompetensi Guru.